ترجمات معاني القرآن الكريم إلى اللغة الصينية (دراسة نقدية تحليلية) - Nooh Ma Yu Long (Universiti Sains Islam Malaysia, 2024)
This study deals with four types of Chinese translations regarding the meaning of the Holy Quran by research study and analysis. It includes eight models of the translations in China that had appeared since the early twentieth century until today. The first type is two models of translation among non-Chinese Muslims, and the second type is two models of translation of Chinese Muslims, quoted from the non-Arab. The third type is two models of translation among Chinese Muslims those who are influenced by the ideas of deviant groups such as Batiniyyah, Qadianiyyah and extreme rationalism or those who adhere to them. While the fourth type, is two models of translation from Shari'ah scholars among Chinese Muslims who translate directly from Arabic language. The main objective of this study is to show the mistakes occurred in translations in the aspect of linguistics and creed. The study also focuses on the right translation through the extrapolation of the texts and analysis. Based on this, the researcher studies a particular part of these translations by doing analytical and critical study, to identify the capacity in delivering the meaning of Holy Quran to the reader. In terms of correct translations, this research through its academic critics relies on the great books of the interpretations among the great scholars. It emphasizes the importance of the correct creed “aqeedah” of the interpreter in true understanding of the Quranic verses on the creedal issues. It is also emphasizing the need to fulfill the conditions of understanding Shari’ah principle and to have proficiency in both Arabic and Chinese language in order to deal with the translation of the Holy Quran. Among the main results reached by the study are that, the translation for most Muslims is the only way to understand the guidance in the Qur'an for their lives. Additionally, the process of Quranic translation must be collective work by detail academic rules, rather than remaining as an individual effort by anybody without the Shari’ah observation. The translators of the Holy Qur'an should be appointed by the institutions related to the Quranic organization so as not to allow the non Muslims from doing translation of the Quranic verses. All translations appear at any time must achieve a sufficient standard of study, criticism and evaluation from different universities and academic institutions.